How I found Livingstone - Stanley, Henry M. (Henry Morton), 1841-1904 (Salt Lake City, UT : Project Gutenberg, 2004)
"How I Found Livingstone" by Sir Henry M. Stanley is a historical account written during the late 19th century. The book chronicles the author's expedition to find the famous explorer Dr. David Livingstone, who had gone missing in Africa while conducting his own explorations. The narrative unfolds through Stanley$1 (Bs own experiences and encounters in Central Africa, as he undertakes the challenging task of locating Livingstone and gathering news about his circumstances. The beginning of the narrative introduces Stanley as he receives instructions from Mr. James Gordon Bennett, the manager of the 'New York Herald', to find Livingstone, who is believed to be lost in Africa. As Stanley prepares for this significant journey, he reflects on the extensive plans required to organize the expedition, including gathering supplies, settling financial arrangements, and hiring an escort. The opening sets the stage for his odyssey, filled with a blend of anticipation and doubt, showcasing Stanley's determination to succeed against the backdrop of danger and uncertainty in the African wilderness. (This is an automatically generated summary.)s
Release date is 2004-02-01
Produced by Geoffrey Cowling and David Widger
Keywords: Africa, Central -- Description and travel; Livingstone, David, 1813-1873